A new pressure vessel design by analysis method avoiding stress categorization. (May 2017) - Li, Hongjun; Huang, Xun; Yang, Peng; Yang, Hui
Abstract: Stress categorization in the design by analysis (DBA) procedure for protection against plastic collapse in pressure vessel has been problematic during application. For example, it is difficult to determine the proportion of primary and secondary stress at the gross structural discontinuities. This paper proposes a new method to avoid the stress categorization by extending the current elastic stress analysis method in ASME Code based on lower bound limit load theory. The proposed method assumes a stress distribution along the stress classification line (SCL) in the form of limit stress state for a beam under membrane and bending load, rather than a linear stress distribution. The effectiveness of proposed method is verified by comparing with the elastic stress analysis, Limit-Load Analysis, Elastic-Plastic stress Analysis of the ASME Code for axisymmetric pressure vessels. The results concluded that the new method is effective easy to use. Highlights: A new method based on lower bound limit load theory was proposed to avoid the stress categorization procedure. The proposed method assumes a stepped stress distribution along the stress classification line (SCL). For continuous regions, both stress categorization and DBA-L procedure produced similar results. The procedure of DBA-L method is explicit and easy to use for engineers.